The “Hoover” (vacuum cleaner) technique for calcifying tendonitis deposits excision and removal of the calcific debris - Ehud, Atoun (Medknow Publications & Media Pvt Ltd, 2012)
A new technical tip for the improvement of the arthroscopic treatment of symptomatic calcifying tendinitis is described. Arthroscopic excision of calcifying tendonitis may result with multiple minute calcific debris in the subacromial bursa, causing severe post operative pain due to chemical irritation of the bursa. We suggest the use of a bladeless shaver barrel as a “Hoover” (vacuum cleaner) for arthroscopic clearance of these miniature calcific debris from the subacromial space after resection of the major deposits. The use of this technique resulted in good clinical outcome with improved post operative pain.